NAD binding site of diphtheria toxin: identification of a residue within the nicotinamide subsite by photochemical modification with NAD. - Carroll, S F (1984)
We showed earlier that exposing mixtures of NAD and diphtheria toxin fragment A to ultraviolet radiation (253.7 nm) induced the formation of covalently linked protein-ligand photoproducts. Here we report that when [carbonyl-14C]NAD was employed in such procedures, the efficiency of labeling of the protein approached 1 mol/mol, and at least 94% of the incorporated label was associated with a single residue, glutamic acid at position 148. Fragment A photolabeled in this manner was enzymically inactive. The efficiency of photolabeling was much lower (less than 0.2 mol/mol) when NAD radiolabeled in either the adenine moiety or the adenylate phosphate was used, and the label was attached to different site(s) within fragment A. Efficient photochemical transfer of label from [carbonyl-14C]NAD occurred under identical conditions with the nucleotide-free form of whole diphtheria toxin, CRM-45, or activated exotoxin A from Pseudomonas aeruginosa, but not with nucleotide-bound diphtheria toxin, CRM-197, native exotoxin A, or any of several NAD-linked dehydrogenases. On the basis of these and other results we suggest that part or all of the nicotinamide moiety of NAD is efficiently transferred to glutamate-148 of fragment A under the influence of ultraviolet irradiation and that this residue is located within the nicotinamide subsite. This location implies that glutamate-148 is at or near the catalytic center of the toxin. Our data provide direct evidence for the location of the NAD site in an ADP-ribosylating toxin and demonstrate highly efficient and specific photolabeling by [carbonyl-14C]NAD.